2008
DOI: 10.1091/mbc.e07-12-1263
|View full text |Cite
|
Sign up to set email alerts
|

Novel Interactions of ESCRT-III with LIP5 and VPS4 and their Implications for ESCRT-III Disassembly

Abstract: The AAA؉ ATPase VPS4 plays an essential role in multivesicular body biogenesis and is thought to act by disassembling ESCRT-III complexes. VPS4 oligomerization and ATPase activity are promoted by binding to LIP5. LIP5 also binds to the ESCRT-III like protein CHMP5/hVps60, but how this affects its function remains unclear. Here we confirm that LIP5 binds tightly to CHMP5, but also find that it binds well to additional ESCRT-III proteins including CHMP1B, CHMP2A/ hVps2-1, and CHMP3/hVps24 but not CHMP4A/hSnf7-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
87
1
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 47 publications
10
87
1
1
Order By: Relevance
“…Thus, LIP5(MIT) 2 can bind MIM1 elements from multiple ESCRT-III proteins but apparently cannot bind MIM2 elements. Our data generally agree well with a previous study (50), except that the equilibrium dissociation constant we measured for the CHMP1B constructs (ϳ3 M) was higher than that in the previous report (EC 50 ϭ 25 nM). In that case, however, the tighter binding measurement may have been enhanced by avidity effects because the experiment was configured so that dimeric LIP5 was binding to immobilized CHMP1B.…”
Section: Lip5 Residues 1-163 Comprise a Tandem Mit Domain-wesupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, LIP5(MIT) 2 can bind MIM1 elements from multiple ESCRT-III proteins but apparently cannot bind MIM2 elements. Our data generally agree well with a previous study (50), except that the equilibrium dissociation constant we measured for the CHMP1B constructs (ϳ3 M) was higher than that in the previous report (EC 50 ϭ 25 nM). In that case, however, the tighter binding measurement may have been enhanced by avidity effects because the experiment was configured so that dimeric LIP5 was binding to immobilized CHMP1B.…”
Section: Lip5 Residues 1-163 Comprise a Tandem Mit Domain-wesupporting
confidence: 92%
“…5. In excellent agreement with a previous report (50), full-length LIP5 bound CHMP5(139 -195) with a dissociation constant of 2.0 Ϯ 0.2 nM, whereas a control LIP5(260 -307) construct corresponding to the C-terminal VSL domain alone bound only very weakly, if at all (K D Ͼ 10 M). Analytical ultracentrifugation analyses confirmed that the LIP5 protein formed a tight dimer, as expected based upon structural studies of the dimeric C-terminal VSL domain (48, 58) (data not shown).…”
Section: Lip5 Residues 1-163 Comprise a Tandem Mit Domain-wesupporting
confidence: 92%
See 3 more Smart Citations